Proportionality as a constitutional ground of judicial review with special reference to human rights. (2nd January 2016) - Simamba, Bilika H.
ABSTRACT: Many countries in the British Commonwealth do not recognize proportionality as a general ground for judicial review. In the Cayman Islands, a British Overseas Territory, the 2009 Constitution provides that decisions of public authorities must, among other things, be proportionate. In the United Kingdom, by virtue of the Human Rights Act 1998 ('HRA'), domestic courts must take into account Strasbourg jurisprudence, which applies the proportionality principle in cases involving the European Convention on Human Rights. This article examines the extent to which proportionality may have become, if at all, a general ground for review in the Cayman Islands. The answer to this question is likely to influence the interpretation of other constitutions (and statutes in general) in the Commonwealth which have codified some aspects of judicial review. The extent to which the HRA is relevant to the interpretation of human rights provisions in the British Overseas Territories is also considered.